2023
DOI: 10.7759/cureus.42736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Different Instrumentation Techniques on the Incidence of Postoperative Pain in Patients Undergoing Root Canal Treatment

Ankita Agrawal,
Neha Agrawal,
Krishna Biswas
et al.

Abstract: Background: Postoperative pain is a common concern in root canal treatment, and the choice of instrumentation technique can significantly impact patient comfort. This study aimed to evaluate the impact of different instrumentation techniques on the incidence of postoperative pain in patients undergoing root canal treatment.Methods: A randomized controlled trial was conducted on 208 patients randomly assigned to four groups: step-back preparation, crown-down preparation, hybrid technique, and conventional instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The evaluation of the GF system was conducted in response to claims that this stainless steel system offers advantages over traditional nickel-titanium files. Additionally, a recent randomized controlled trial discovered that patients reported a reduction in pain intensity when the manual step-back approach was utilized, as compared to other commonly employed techniques such as crown-down, hybrid, and conventional instrumentation [ 15 ]. The aforementioned observation implies that the utilization of the step-back technique could potentially lead to a reduction in the extrusion of debris.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of the GF system was conducted in response to claims that this stainless steel system offers advantages over traditional nickel-titanium files. Additionally, a recent randomized controlled trial discovered that patients reported a reduction in pain intensity when the manual step-back approach was utilized, as compared to other commonly employed techniques such as crown-down, hybrid, and conventional instrumentation [ 15 ]. The aforementioned observation implies that the utilization of the step-back technique could potentially lead to a reduction in the extrusion of debris.…”
Section: Discussionmentioning
confidence: 99%
“…The step-back technique enlarges the canal in a graduated manner by using sequentially larger files. A recent randomized controlled trial found that patients experienced less intense pain with the manual step-back approach versus other common techniques such as crown-down, hybrid, and conventional instrumentation [ 15 ]. This suggests that the step-back technique may result in less debris extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, varying root canal instrumentation systems appear to be linked to varying degrees of extrusion [13][14][15][16]. Some research reveals higher levels of extruded contaminants following the use of hand endodontic files instead of engine-driven endodontic files [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%